Acute Exacerbations of Chronic Obstructive Pulmonary Disease: Diagnosis, Management, and Prevention in Critically Ill Patients. Issue 6 (1st June 2015) - Dixit, Deepali; Bridgeman, Mary Barna; Andrews, Liza Barbarello; Narayanan, Navaneeth; Radbel, Jared; Parikh, Amay; Sunderram, Jag
<x xml:space="preserve">Abstract</x> Chronic obstructive pulmonary disease (COPD) is the third leading cause of death and is a substantial source of disability in the United States. Moderate‐to‐severe acute exacerbations of COPD (AECOPD) can progress to respiratory failure, necessitating ventilator assistance in patients in the intensive care unit (ICU). Patients in the ICU with AECOPD requiring ventilator support have higher morbidity and mortality rates as well as costs compared with hospitalized patients not in the ICU. The mainstay of management for patients with AECOPD in the ICU includes ventilator support (noninvasive or invasive), rapid‐acting inhaled bronchodilators, systemic corticosteroids, and antibiotics. However, evidence supporting these interventions for the treatment of AECOPD in critically ill patients admitted to the ICU is scant. Corticosteroids have gained widespread acceptance in the management of patients with AECOPD necessitating ventilator assistance, despite their lack of evaluation in clinical trials as well as controversies surrounding optimal dosage regimens and duration of treatment. Recent studies evaluating the safety and efficacy of corticosteroids have found that higher doses are associated with increased adverse effects, which therefore support lower dosing strategies, particularly for patients admitted to the ICU for COPD exacerbations. This review highlights recent findings from the current body of evidence on nonpharmacologic and pharmacologic treatment and prevention of AECOPD in critically ill patients. In addition, the administration of bronchodilators using novel delivery devices in the ventilated patient and the conflicting evidence surrounding antibiotic use in AECOPD in the critically ill is explored. Further clinical trials, however, are warranted to clarify the optimal pharmacotherapy management for AECOPD, particularly in critically ill patients admitted to the ICU.